PERBANDINGAN TAKSIRAN ZAKAT PERTANIAN DI NEGERI-NEGERI TERPILIH DI MALAYSIA: The Comparative Assessment of Agricultural Zakah in Selected States in Malaysia - Ab Rahman, Muhamad Firdaus; Abdullah, Luqman; Ali, Nor Aini (Jurnal Syariah, 2015)
The administration and management of zakah is under the jurisdiction of State Islamic Religious Councils. Thus, the assessment of zakah on agricultural produce is based on policies, enactment or fatwas’ determined in the state. This article will analyse the assessment of zakah on agricultural products by the zakah institutions and State Mufti Department in a number of states namely Selangor, Penang, Perlis, Terengganu and Sarawak. The analysis will take into account several matters such as the taxable rate, the nisab and the assessment method of assessment. The data for this study has been obtained mainly through interview. The research shows that zakah institutions in the selected states have applied different taxable rates ranging from 5%-10%. The nisabs that they use have also been found to be different which are between 363 to 400 bushels. In the assessment procedure, it is found that the majority of the zakah institutions observed have deducted the cost of plantation operation from the basic taxable income.